Seismic performance of URM buildings with in-plane non-stiffened and stiffened timber floors. (15th July 2018) - Scotta, Roberto; Trutalli, Davide; Marchi, Luca; Pozza, Luca
Highlights: The seismic response of masonry buildings with stiffened timber floors is analysed. Two case-study buildings have been analysed using 3D numerical models. Results of the non-linear dynamic analyses are presented for different PGA values. Abstract: The seismic response of un-reinforced masonry buildings due to in-plane stiffening of their single-layer timber floors is numerically investigated by means of non-linear incremental dynamic analyses. Two independent case studies of two-storey buildings with timber floors stiffened with alternative techniques (addition of 45° oriented timber boards, of steel plates or of a 50-mm thick reinforced-concrete slab) have been analysed using three-dimensional numerical models. The non-linear elements of the models have been calibrated on experimental data available in literature to reproduce the actual hysteretic behaviour of both masonry and floors. Results of the non-linear incremental dynamic analyses are presented for different Peak Ground Acceleration values, to quantify the different seismic effectiveness of the building achieved with each stiffening method. Main findings show that, for the considered geometry and properties of the case studies, even not infinitely stiff floors are able to confer a good seismic behaviour to un-reinforced masonry buildings. On the contrary, their seismic capacity may decrease if a retrofitting method leading to excessive floor stiffening is adopted.